The Students' Mastery of Modal Auxiliary at the Second Year of SMP Negeri 5 Malangke - Fibri Indira Lisanty; Musfira (FOSTER: Journal of English Language Teaching, 2021)
This research aims to determine the students’ mastery in using modal auxiliary at second grade of SMP Negeri 5 Malangke. This research applied descriptive quantitative method as the research design. the population of this research is class XII of SMP Negeri 5 Malangke. This research used all the students at the second grade of SMP Negeri 5 Malangke as the population of this research. The total number of population from this research is 125 and the total sample of this research is 20 students. The researcher uses purposive sampling as the technique in determining the sample. This research used test as a instrument of this research. The results of this research indicated that the students’ mastery in using modal auxiliary at second grades of SMP Negeri 5 Malangke is still low. It can be proven from the average of this research. The average of this research is 40, it means that almost the students have low mastery in vocabulary. Therefore, the researcher concluded that the students’ mastery in using modal auxiliary at second grades of SMP Negeri 5 Malangke is poor.